Development Strategy Of The Creative Economy In The Culinary Subsector: The Case Of “Selera” Petis Crackers In Kendal Regency - Haqi, Dita Nafaliya Dinul; Pujiati, Amin; Widiyanto (Journal of Economic Education, 2025)
This study maps the strengths, weaknesses, opportunities and threats of development for the Kerupuk Petis Selera business in Kendal Regency, to assess and take the right strategy in overcoming existing obstacles. This type of research is qualitative using the SWOT method by distributing questionnaires, as well as direct interviews with business owners and supported by extracting data from key people related to indicators of strengths, weaknesses, opportunities and threats of marketing and processing petis crackers. The results or findings found are that SWOT analysis can help in mapping the research framework that identifies externally and internally which includes human resources, management systems, from marketing and product quality so that it can facilitate strategic decision making to improve business quality and long-term planning. Where the best strategy found is the ST strategy such as; 1). Make variations of other processed products made from the same base; 2). Innovation in packaging that is suitable for souvenirs; 3). Utilizing other technologies.